2016
DOI: 10.3390/molecules21121705
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Traditional Chinese Medicines: Extraction, Purification, Modification, and Biological Activity

Abstract: Traditional Chinese Medicine (TCM) has been used to treat diseases in China for thousands of years. TCM compositions are complex, using as their various sources plants, animals, fungi, and minerals. Polysaccharides are one of the active and important ingredients of TCMs. Polysaccharides from TCMs exhibit a wide range of biological activities in terms of immunity-modifying, antiviral, anti-inflammatory, anti-oxidative, and anti-tumor properties. With their widespread biological activities, polysaccharides consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(88 citation statements)
references
References 195 publications
(243 reference statements)
0
87
0
1
Order By: Relevance
“…Polysaccharides have been recognized as one of the substances used worldwide in food preparation and processing as thickeners, emulsifiers, or stabilizers (Hu, Nie, Li, Wang, & Xie, 2017). Numerous studies have reported that polysaccharides have anticancer, antioxidant, and antibacterial activities (Chen, Yao, et al, 2016;Li, Yuan, Zhou, Zeng, & Lu, 2016;Ou, Yu, Zhang, & Zhu, 2016;Wang, Liu, Huang, & Zhang, 2016). Certain studies have shown that aqueous and ethanol extracts of the rhizome of Osmunda japonica Thunb possess antifungal activity (Zhu et al, 2013).…”
mentioning
confidence: 99%
“…Polysaccharides have been recognized as one of the substances used worldwide in food preparation and processing as thickeners, emulsifiers, or stabilizers (Hu, Nie, Li, Wang, & Xie, 2017). Numerous studies have reported that polysaccharides have anticancer, antioxidant, and antibacterial activities (Chen, Yao, et al, 2016;Li, Yuan, Zhou, Zeng, & Lu, 2016;Ou, Yu, Zhang, & Zhu, 2016;Wang, Liu, Huang, & Zhang, 2016). Certain studies have shown that aqueous and ethanol extracts of the rhizome of Osmunda japonica Thunb possess antifungal activity (Zhu et al, 2013).…”
mentioning
confidence: 99%
“…В составе растительной клетки присутствуют свободные моносахариды, водорастворимые полисахариды, пектиновые вещества, целлюлозы и гемицеллюлозы. Выделение сахаров из растительного сырья происходит в несколько этапов [8]. Первым шагом является обезжиривание, для этого обычно применяют экстракцию по Сокслету с использованием органического растворителя, такого как петролейный эфир и 95% этанол, этот шаг обязателен для богатых липидами растений.…”
Section: извлечение углеводов из растительного сырьяunclassified
“…And APS is safe without any distinct toxicity and side effects [9], thus can be used for a long time. However, APS is mainly extracted using water extraction method, which has several disadvantages, such as low active ingredients (polysaccharide content), especially the yield (only about 2.5%) of crude APS [10], and high cost. All of these limit the development and utilization of APS.…”
Section: Introductionmentioning
confidence: 99%